IMPLEMENTASI KEBIJAKAN PEMBERLAKUAN PEMBATASAN KEGIATAN MASYARAKAT (PPKM) DARURAT UNTUK PENANGGULANGAN GELOMBANG KE-2 KASUS COVID-19 DI DKI JAKARTA. - Anastasia Feliciani (2023)
This study aims to identify and analyze the implementation of the PPKM policy carried out by the Covid-19 Task Force in the DKI Jakarta area, as well as to determine the extent of the PPKM policy's role in changing the behavior of the people of DKI Jakarta to deal with the Covid-19 pandemic and the impact of the PPKM policy in dealing with the Covid-19 pandemic. 19 on the socio-political dynamics in DKI Jakarta Province. The method used is descriptive qualitative using primary data sources and secondary data. The sampling technique was carried out by purposive sampling. Researchers used four stages of data analysis according to Miles & Huberman, namely data collection, data reduction, data presentation. The purpose of this study was to find out the implementation phenomenon and the various impacts of the PPKM policy carried out by the Covid-19 Task Force in the DKI Jakarta area.The final results of this study show that the implementation of PPKM by the Covid-19 Task Force in the DKI Jakarta area is an administrative public policy that is carried out through adoption and alignment with various provisions and regulations formulated by the central government which was then followed up by the Provincial Government of DKI Jakarta by issuing three regulations namely Instruksi Gubernur DKI Jakarta Nomor 22 Tahun 2020, Peraturan Gubernur DKI Jakarta Nomor 3 Tahun 2021, serta Peraturan Gubernur DKI Jakarta Nomor 23 Tahun 2020. From this study it can be concluded that implementation of PPKM by the Covid-19 Task Force in the DKI Jakarta area is technically carried out through a strategy of keeping distance and avoiding crowds carried out by some DKI Jakarta residents and compared to other PPKM strategies this program is the most difficult to implement and has strong links with economic and development factors social. The implementation of PPKM in the DKI Jakarta area has received various responses from the community, where there are community groups that support the PPKM policy, but there are groups who think that this policy has not been effective. The impact of PPKM implementation in the DKI Jakarta Province area can be divided into two, namely the positive impact, namely a decrease in the positive number of Covid-19 which indicates effective control, while the negative impact is the socio-economic depreciation which causes poverty in several layers of society in DKI Jakarta.